Microbes are not bound by sociobiology: Response to Kümmerli and Ross-Gillespie (2013) - Rainey, Paul B.; Desprat, Nicolas; Driscoll, William W.; Zhang, Xue-Xian (Evolution, 2014)
In recent years, sociobiology has been extended to microorganisms. Viewed through this lens, the microbial world is replete with cooperative behaviors. However, little attention has been paid to alternate hypotheses, making many studies self-confirming. Somewhat apart is a recent analysis of pyoverdin production—a paradigmatic public good and social trait—by Pseudomonas, which has revealed discord between predictions arising from sociobiology and the biology of microbes. This led the authors, Zhang and Rainey (Z&R), to question the generality of the conclusion that pyoverdin is a social trait, and to question the fit between the sociobiology framework and microbiology. This has unsettled Kümmerli and Ross-Gillespie (K&R), who in a recent "Technical Comment" assert that arguments presented by Z&R are flawed, their experiments technically mistaken, and their understanding of social evolution theory naive. We demonstrate these claims to be without substance and show the conclusions of K&R to be based on a lack of understanding of redox chemistry and on misinterpretation of data. We also point to evidence of cherry-picking and raise the possibility of confirmation bias. Finally, we emphasize that the sociobiology framework applied to microbes is a hypothesis that requires rigorous and careful appraisal.